Water wave scattering by a sinusoidal bed in the presence of vertically sheared current. (March 2021) - Laffitte, E.; Rey, V.; Touboul, J.; Belibassakis, K.
Highlights: Laboratory experiment of wave propagation in the presence of opposing sheared current. Wave scattering by sinusoidal bed in the presence of sheared current, Bragg resonance. Influence of sheared current on resonant peak location and amplitude. Abstract: Wave scattering over a sinusoidal bottom in the presence of a vertically sheared current is investigated experimentally and compared with a modified-mild slope model taking into account a linear vertical shear. Waves were generated in a flume without or with an opposing sheared current and propagated over a patch of 10 sinusoidal bars before dissipating on a beach. The shear of the current was controlled using a perforated screen. The Doppler shift of resonant Bragg frequency in the presence of a sheared current is observed. The modified mild-slope model taking into account both incoming and reflected waves predicts both the location and the amplitude of the peak of reflection at the Bragg resonance conditions, which are found to be sensitive to both the surface current intensity and the vertical shear.